ACTIVITY PROGRAMMING IN MEMORY CARE: WHICH ACTIVITIES ARE ASSOCIATED WITH HIGHEST AFFECT IN PERSONS WITH DEMENTIA?. (11th November 2018) - Fauth, E; Rose, C; Meyer, K
Abstract: Activities can increase quality of life for residents with dementia, however determining which activities are high in quality is often subjective. In this study, trained researchers observed 22 residents in common areas of a memory care unit (10 males, 12 female, all consented for research). Assessments occurred in 15-minute sessions across multiple days (totaling 7000 minutes). Each minute involved co-observation of staff interactions (Quality Interaction Scale, Dean, et al., 1993) and residents' positive affect (Philadelphia Geriatric Center Affect Rating Scale, Lawton, et al., 1996). Observers noted types of activities underway. Z-scores indicated proportionally higher positive affect in residents during preplanned activities, compared to non-facilitated/unplanned activities (z = -3.09, p < .001). Compared to residents' positive affect during "no activity", positive affect was proportionally highest (p < .001) during music therapy (z = -23.43) and motor activity (z = -13.67), and lowest (p = n.s.) during dance performances (z = -1.07) and art/crafts (z = 1.83). Compared to positive staff interactions during "no activity", positive staff interactions was proportionally highest (p < .001) during motor activities (z = -12.74) and music therapy (z = -11.86), and lowest (p = n.s.) during cognitive activities (z = -0.30) and music presentations (z = -0.17). Commonalities in quality activities included residents being able to see, engage, and move about if they wanted, staff considering residents' autonomy and staff using active efforts to converse with residents. Staff can observe affect in residents to evaluate engagement during activities, and adjust delivery and interaction frequency where needed.